Detection of myocardial disorders by magnetic resonance spectroscopy. - Hudsmith, L; Neubauer, S (2008)
Magnetic resonance spectroscopy (MRS) utilizes magnetic resonance signals from nuclei, such as phosphorus-31, to provide information regarding the biochemical composition and metabolic state of cardiac muscle. This technique is the only method available for noninvasive assessment of cardiac metabolism without the need for the application of external radioactive tracers. MRS provides insights into the role of cardiac energetics in ischemic heart disease, heart failure, hypertrophy, and valve disease. Furthermore, response to therapeutic intervention can be monitored using this method. At present, this technique is used as a research tool, because low spatial and temporal resolution, as well as low reproducibility, precludes its diagnostic use in clinical practice; however, higher-field magnetic resonance systems-using, for example, 7 T-will enable improvements in resolution and reproducibility that may take cardiac MRS into the clinical realm.